Pelatihan Dan Pendampingan Dai Cilik Dalam Kegiatan Kuliah Kerja Nyata Di Korong Lapau Jambu Nagari Sungai Durian - M. Riski Ilham; Joni Indra Wandi; Nurva Dillatul Vatin; Nurshopia Wati; Ghaniyatul Ilmi; Mhd Ikhwan; Metri Revidawati; Ulfa Mayura (Universitas Sumatera Barat, 2024)
Training and mentoring for dai cilik is onne of the main programs in real work lecture (kkn) activities in korong lapau jambu, nagari sungai durian. This program aims to equip children with basic da’wah skills and form strong islamic character from an early age. The method used by the participatory action research (par) approach includes interactive learning, lecture simulation, and intensive mentoring that focuses on developing public speaking skills, mastery of religgious material, and preaching ethics. It is hoped that the results of this training can create a young generation who not only have good knowledge of religion, but are also able to become agents of positive change in their environment. Program evaluation showed a significant increase in participants’ self-confidence and preachinng abilities, as well as a positive response from the local community to this activity. It is hoped that this program can become a model for similiar efforts in other regions.